KONJO-BUGINESE LANGUAGE ACCOMMODATION IN INTERACTION WITH THE IMMIGRANTS IN WEST SINJAI - Hasminah Said; Tuti Bahfiarti; Muhammad Farid (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aimed to identify the use of Konjo-Buginese language in West Sinjai, Sinjai Regency and the Konjo-Buginese language accommodation in interacting with the immigrants. This study employed the ethnography theory by Dell Hymes. The data were gathered using in-depth interview, observation, and documentation and analyzed using the communication accommodation theory by Howard Giles. The results showed that Konjo-Buginese language used in West Sinjai was adopted mostly from the Konjo Mountains language and the accommodation took the form of convergence. The divergent speech behavior was only performed by the elderly people and those who do not speak Indonesian.